Comparative environmental impact assessment on a pharmaceutically interesting compound - Akakios, Stephanie Gina (My University, 2021)
This dissertation entails an early stage comparative ‘greenness’ evaluation on three current synthetic pathways to bis-THF alcohol –a key active subunit used in a class of ARV’s that shows high efficacy in combating multi-drug resistance of various HIV strains. The three most recent and innovative bis-THF alcohol synthesis routes that were assessed include route A (Hayashi, Aikawa, Shimasaki, Okamoto, Tomioka, Miki, Takeda and Ikemoto, 2016), route B (Sevenich, Liu, Arduengo III, Gupton and Opatz, 2017) and route C (Moore, Stringham, Teager and Yue, 2017). The aim was to find the most eco-efficient bis-THF alcohol synthesis route using green chemistry metrics, principles, guides and web-based tools. The assessment strategy entailed examining each synthetic pathway with specific focus on waste generation (E -factors), process greenness relative to industrial benchmarks (iGALTM), the quantities and nature of solvent used (Solvent Intensity and GSK solvent guide), Green MotionTM and the principles of green chemistry in general. In understanding the challenges that lie in combining assessment methods to effectively compare the greenness between synthetic routes, when faced with green alternatives, the most eco-efficient synthetic pathway was found to be route Bentire one-pot procedure, adhering to most of the green chemistry principles, returning good metric and assessment results whilst further being most economically feasible against its comparators. Route A reported by Hayashi et al., (2016), involved a stereo selective catalytic cross aldol reaction between polymetric ethyl glyoxylate and a protected aldehyde. Route A entire step-by-step afforded an overall yield of 54% over 5 synthesis steps, a reaction complexity of 4 and a cumulative E-factor of 14.54.Route B reported by Sevenich et al., (2017), involved a photocycloaddition between furan and a protected glycol aldehyde, followed by the hydrogenation and lipase catalysed enzymatic resolution. The furan starting materials as well as many other reagents used in the synthetic pathway were reportedly derived from renewable woody biomass. The protected glycol aldehyde was considered an advanced starting material requiring its own synthetic pathway to be assessed. Further, for route B both a step-by-step procedure as well as a one pot procedure were assessed. The route Bentire step-by-step including the advanced starting material synthesis had an overall yield of 24% over 5 synthesis steps, a reaction complexity of 4 and a cumulative E-factor of 126.77. Combining the advanced starting material with the main synthesis as a one-pot procedure afforded an overall yield of 23% over 2 synthesis steps, a reaction complexity of 4 and cumulative E-Factor of 89.69 and more efficient, environmentally and economically more favourable than the step-by-step procedure. Route C reported by Moore et al., (2017) uses a natural starting material, optically pure monopotassium isocitrate that is obtained from a high-yielding fermentation process, thus eliminating the need for enzymatic resolution and did not require an advanced starting material. The merit of route C was the early positioning of the resolution step. Both a step-by-step and a partial one-pot procedure were assessed. The overall yield of the former was 50% over 5 synthesis steps, with a reaction complexity of 2 and E-factor of 124.84. For the one-pot procedure the overall yield was 44% over 3 synthesis steps, with a reaction complexity of 2 and E-Factor of 273.37 .The one-pot procedure aided in condensing the synthetic pathway but required an increase in solvent quantities thus performing worse environmentally and economically than the step-by-step procedure. From the iGALTM methodology, route A entire step-by-step was found to have ‘excellent’ mass-efficiency with the lowest E-factor of 14.54, generating 84% and 88% less solvent and water waste than route Bone-pot and C step-by-step respectively. Solvent materials were found to be the largest waste contributors (~ 53%) and the greatest environmental concern in all three synthetic pathways. Thus, solvent utilization offers the greatest potential in reducing the E-factor of bis-THF alcohol synthesis both qualitatively and quantitatively for all pathways. Route B entire one-pot showed that 80% of its total solvent mass were green solvents (EtOAc and MeOH), making it the least impactful, safest and most cost effective synthetic pathway saving up to 51% compared to route A and C procedures. Conversely route C procedures comprised of 95% hazardous and problematic solvents requiring > 500kg solvents per kg product, resulting in the most costly and wasteful synthetic pathway with health and safety issues. The Green MotionTM tool predicts route Bone-pot procedure to be the most sustainable owing to its unique combination of green chemistry techniques including one-pot procedure, bio-catalysis, ambient reaction conditions, reasonable amounts of green solvents and renewable raw materials originating from woody bio-mass. Conversely route Cone-pot was predicted to be the least sustainable pathway owing to the variety of energy intensive process operations (i.e., distillation, crystallization, multiple heating and cooling), large amounts of solvent materials used and high waste generation in synthesizing bis-THF alcohol. From an economic perspective, the total synthesis cost of route B entire one-pot procedure was found to be most economical with route A and C being1.7 and 4.3 times more expensive respectively. From a collective and comparative assessment using a radial polygon, it was found that route Bone-pot procedure covered the highest polygon area at 85% thus performing best across multiple greenness assessments. The radial polygon ranked the synthetic pathways from best to worst across multiple greenness assessments as: route Bone-pot, route B step-by-step, route A step-by-step, route C step-by-step and route Cone-pot procedure. Finally, Route Bone-pot procedure was found to be the most environmentally friendly and economical (eco-efficient) sustainable synthetic pathway to the bis-THF alcohol scoring the overall best amongst all assessment criteria
A dissertation submitted to the Faculty of Engineering and the Built Environment, University of the Witwatersrand, in partial fulfilment of the requirements for the degree of Master of Science in Engineering, 2021